Transcription factor c-Rel mediates communication between commensal bacteria and mucosal lymphocytes. Issue 5 (8th October 2021) - Luu, Maik; Binder, Kai; Hartmann, Sabrina; Kespohl, Meike; Bazant, Jasmin; Romero, Rossana; Schütz, Burkhard; Steinhoff, Ulrich; Visekruna, Alexander
Abstract: The NF-κB transcription factor c-Rel plays a crucial role in promoting and regulating immune responses and inflammation. However, the function of c-Rel in modulating the mucosal immune system is poorly understood. T follicular helper (Tfh) cells and IgA production in gut-associated lymphoid tissues (GALT) such as Peyer's patches (PPs) are important for maintaining the intestinal homeostasis. Here, c-Rel was identified as an essential factor regulating intestinal IgA generation and function of Tfh cells. Genetic deletion of c-Rel resulted in the aberrant formation of germinal centers (GCs) in PPs, significantly reduced IgA generation and defective Tfh cell differentiation. Supporting these findings, the Ag-specific IgA response to Citrobacter rodentium was strongly impaired in c-Rel-deficient mice. Interestingly, an excessive expansion of segmented filamentous bacteria (SFB) was observed in the small intestine of animals lacking c-Rel. Yet, the production of IL-17A, IgA, and IL-21, which are induced by SFB, was impaired due to the lack of transcriptional control by c-Rel. Collectively, the transcriptional activity of c-Rel regulates Tfh cell function and IgA production in the gut, thus preserving the intestinal homeostasis. Graphical Abstract: The transcription factor c-Rel regulates intestinal homeostasis and protects against pathogen colonization; c-Rel-deficient mice display defective IgA production in the intestine.